1982
DOI: 10.1177/036354658201000402
|View full text |Cite
|
Sign up to set email alerts
|

The Medial Tibial Stress Syndrome

Abstract: The medial tibial stress syndrome is a symptom complex seen in athletes who complain of exercise-induced pain along the distal posterior-medial aspect of the tibia. Intramuscular pressures within the posterior compartments of the leg were measured in 12 patients with this disorder. These pressures were not elevated and therefore this syndrome is a not a compartment syndrome. Available information suggests that the medial tibial stress syndrome most likely represents a periostitis at this location of the leg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(75 citation statements)
references
References 8 publications
3
69
0
1
Order By: Relevance
“…In particular, the bone scan was used to detect stress fractures of the rib in rowers, and MR images provided a rapid, anatomically precise diagnosis of stress fractures of the ulnar olecranon in baseball pitchers without additional radiation exposure. The uptake of technetium 99m, particularly in the tibial diaphysis, has had various interpretations; localized focal uptake of technetium 99m suggests a stress fracture (Figure 1), whereas its linear uptake along the periosteum suggests periostitis or stress syndrome (shin splints) [13][14][15] . Therefore, the tibiae showing localized focal uptake but not linear uptake of technetium 99m were diagnosed as having a stress fracture.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the bone scan was used to detect stress fractures of the rib in rowers, and MR images provided a rapid, anatomically precise diagnosis of stress fractures of the ulnar olecranon in baseball pitchers without additional radiation exposure. The uptake of technetium 99m, particularly in the tibial diaphysis, has had various interpretations; localized focal uptake of technetium 99m suggests a stress fracture (Figure 1), whereas its linear uptake along the periosteum suggests periostitis or stress syndrome (shin splints) [13][14][15] . Therefore, the tibiae showing localized focal uptake but not linear uptake of technetium 99m were diagnosed as having a stress fracture.…”
Section: Methodsmentioning
confidence: 99%
“…33,34,39 Medial tibial stress syndrome (MTSS) is an exercise-induced, localized pain along the distal two thirds of the posterior-medial tibia and can be a debilitating injury in runners. 11,18,27,28,43 In studies of recreational runners, MTSS has been reported as the most 41 or second most frequently diagnosed injury. 8 Clement et al 8 reported that the incidence of MTSS was higher among female runners (16.8%) than male runners (10.7%).…”
mentioning
confidence: 99%
“…Mubarak et al 16 found histological signs of periostitis and vasculitis in fascial samples from two cases of MTSS and regarded this condition as a separate entity from CECS. Johnell et al 35 examined bone and soft tissue samples (consisting of fascia and periosteum) in patients surgically treated for medial tibial pain, the diagnosis of which was broad and did not distinguish between CECS and MTSS.…”
Section: Inflammatory Findingsmentioning
confidence: 99%
“…14 There has been variability in the terminology used to describe CECS and other causes of exercise induced lower leg pain such as medial tibial syndrome, 15 medial tibial periostitis, 16 and medial tibial stress syndrome, 16 17 the pathology of which may all merge with CECS. For the purpose of this paper, the clinical entity characterised by exercise induced, inflammatory medial tibial pain with palpatory tenderness of the posteromedial tibial border and often accompanied by patchy linear bony uptake on bone scintigraphy will be referred to as medial tibial stress syndrome (MTSS).…”
mentioning
confidence: 99%